Epidemiological interventions for university students affected by COVID-19 in Erbil, Kurdistan – Iraq - Abdullah, Zheen; Ganjo, Aryan; Shareef, Suhayla; Jawad, Rawand (HMU Conference Proceedings, 2025)
Background and Objectives: The outbreak of SARS-CoV-2 in Wuhan, China in late December 2019 became the harbinger of the COVID-19 pandemic. The main aims of this study is to determine the demographic and clinical characteristics of COVID-19 in the population of the universities in Erbil, Kurdistan-Iraq. As well as results of IgG/IgM in COVID-19 patients are also highlighted in this study. Material and method: A total of 100 recorded data for the COVID -19 isolated from the patients were collected within (10) months (November 2020 until August 2021) from universities in Erbil city, Kurdistan – Iraq. Descriptive statistics was used for analysis. Results: A total of 100 samples were taken from three universities (52 from Hawler Medical University, 35 from University of Kurdistan Hawler and 13 from Tishk International University), from these 32 were male and 68 were female with age arranged between 17-29 years old. Moreover 81 of patients their positive results were confirmed with IgG/IgM test while 19 of them were negative with this test. However, 94% of patients none suffer from other diseases (cardiovascular disease, asthma, diabetes, cancer, hypertension, bronchitis) while 2% suffer from diabetes and 4% from asthma. Indeed, the patients used different medications during treatment, 18% of them treated with Favipiravir, 66% of them used Azithromycin, 5 % consumed Enoxaparin, 8 % Dexamethasone and 3 % treated with ceftriaxone IV. On the other hand, 83 of patients were nonsmokers and 17 of them were smokers.